An Evaluation of Corrosion Pits in Esthetic Coated Stainless Steel Orthodontic Archwires in Dry and Wet Environment at Different Intervals (An In Vitro Study) - JafaKhialar, Shaimaa K; Al-Sheakli, Iman I (Journal of Baghdad College of Dentistry, 2016)
Background: The demand for esthetic orthodontic appliances is increasing; so the esthetic orthodontic archwires were introduced. Among them, Teflon and Epoxy coated stainless steel archwires. The amount of force available from the archwire depends on the structural properties and susceptibility to corrosion. All metallic alloys are changed during immersion in artificial saliva, chlorhexidine mouthwash andtoothpaste, but their behaviors differ from one type to another. They corrode at different rates, which lead to decrease the amount of force applied to the teeth. This in vitro study was designed to evaluate the corrosion pits in stainless steel archwires coated with Teflon and with Epoxy in dry and after immersion in artificial saliva, chlorhexidine(0.2%( (Parodontax) and toothpaste media (Sensodyne) for (1, 7 and 28) days intervals. Moreover, this study is intended to compare the corrosion pits for each type of archwires at these different media among all intervals.Materials and Methods: In this study, two hundred forty pieces of orthodontic wires of Teflon (Hubit) coated Stainless steel (120 pieces) and epoxy (Orthotechnology) coated Stainless steel (120 pieces), rectangular in cross section, size (0.019 x 0.025) inch and 15mm in length divided into four groups according to immersion media: (dry environment group, artificial saliva group, chlorhexidine group and toothpaste group). The atomic force microscope was used to measure the corrosion pits for all samples at dry and wet conditions and after different immersion periods.Results: Statistical analysis showed that there was a highly significant increase in the corrosion pits of Teflon coated stainless steel archwires (P â‰¤ 0.05) in wet environment at 28 days immersion period.The highest corrosion pits were found in the toothpaste medium for the two archwire types at 28 days immersion period.Conclusion: We can conclude that Epoxy coatedstainless steel archwires are indicated to be used above Teflon coated stainless steel archwires in terms of corrosion resistance. IfTeflon coated stainless steel archwires should to be used, they should be change in shorter periods than Epoxy coated stainless steel archwires typeKey words: Esthetic coated archwire, corrosion, Teflon, Epoxy, wet environment, AFM.